Antifungal Study of the Resinous Exudate and of Meroterpenoids Isolated from Psoralea Glandulosa (Fabaceae) - Santander-Meyer, R (2012)
Ethnopharmacological relevance: Psoralea glandulosa L. (Fabaceae) is a medicinal resinous shrub used in Chilean folk medicine as antiseptic in treatment of infections and skin diseases caused by bacteria and fungus. Aim of the study: To evaluate the in vitro antifungal activity of the resin and the active components from P. glandulosa against clinical yeast isolates. Materials and methods: Active compounds were obtained of the resinous exudate from aerial parts of P. glandulosa. Eight species of yeast were exposed to the resin and two major compounds. Minimum inhibitory concentration (MIC80) was determined according to the standard broth microdilution method. Results: Bakuchiol and 3-hydroxy-bakuchiol demonstrated potent activity with the MIC 80 ranging from 4 to >16 and 0.125 to 16 ?g/mL, respectively. The resin had some degree of antifungal activity. Conclusions: The overall results provided important information for the potential application of the 3-hydroxy-bakuchiol from P. glandulosa in the therapy of serious infection and skin diseases caused by clinical yeast. © 2012 Elsevier Ireland Ltd.